Digital Resilience Research Trends: A Bibliometric Analysis (2020–2025) - Sari, Bella Ayu Kartika; Elly Malihah Setiadi; Siti Komariah (Universitas Muhammadiyah Yogyakarta, 2026)
The rapid evolution of digital technology has transformed patterns of communication, social interaction, and the dynamics of society, creating a need for adaptability known as digital resilience. This study aims to conduct a bibliometric analysis to identify research trends, identify clusters or themes in scientific publications on digital resilience, and explore potential research gaps in this field. A bibliometric approach was employed to provide a systematic mapping that can serve as a foundation for future research development. The data sources for this study were obtained from Google Scholar and ScienceDirect using the keywords “digital resilience” and “online resilience,” and were analyzed using VOSViewer. A total of 870 scientific publications were collected from the years 2020–2025. The findings indicate a year-over-year increase in scientific publications on digital resilience over the past five years. Additionally, there has been an increase in publications using keywords such as digital transformation, cybersecurity, artificial intelligence, mental health, and social media, indicating that digital resilience research is multidimensional. This study is expected to contribute to mapping trends and advancing future research related to digital resilience